A 3rd order low-pass filter with high linearity and tunable in-band attenuation for WiMAX/LTE receiver - Gholamreza Zare Fatin (Universiti Malaysia Perlis (UniMAP), 2019)
Link to publisher's homepage at http://ijneam.unimap.edu.my